The Different Effects of Skeletal Muscle and Fat Mass on Height Increment in Children and Adolescents Aged 6–11 Years: A Cohort Study From China - Wu, Dingting; Shi, Liuhong; Xu, Qiongying; Zeng, Yuanyuan; Lin, Xihua; Li, Xiaolin; Zhao, Hanxin; Zhu, Zhihong; Fu, Yeliu; Li, Hong; Dong, Xuehong (Frontiers in Endocrinology, 2022)
Objective This study aimed to investigate the contribution of body composition including skeletal muscle mass (SMM) and body fat mass (BFM) to longitudinal growth among children and adolescents aged 6–11 years old. Methods This cohort study was conducted from the annual health examination between 2019 and 2020. Annual height gain and weight gain and changes in SMM and BFM were calculated and compared between sexes, different nutritional status, and growth curve shifting mode. Spearman analyses and multiple linear regression analysis were performed to identify the impact of SMM, BFM, or body mass index (BMI) on height gain. Results Of the 584 subjects, the annual height gains of boys (4.76 cm in the 6–9-year group and 4.63 cm in the 10–11-year group) were significantly lower than those of girls (5.48 and 5.74 cm, respectively). Spearman analysis showed that SMM gain and height gain were positively and significantly correlated in each examination of all children (r = 0.535 for boys and 0.734 for girls, p < 0.001). Conversely, BFM and height gains were negatively (r = -0.5240 for boys and -0.232 for girls, p < 0.001) correlated. Multiple linear regression analysis identified SMM gain as an independent predictor (95% CI: 1.20,1.44) of height gain after adjusting for age, gender, BMI, BFM gain, and percentage of body fat (PBF). Conclusion SMM gains, rather than BFM gains, were associated with height gains in children and adolescents aged 6–11 years. Monitoring SMM changes in routine healthcare might motivate children and adolescents to achieve dietary and exercise recommendations, thereby growing taller without gaining excessive weight.